2013
DOI: 10.1002/jat.2959
|View full text |Cite
|
Sign up to set email alerts
|

Combined antitumor effects of bee venom and cisplatin on human cervical and laryngeal carcinoma cells and their drug resistant sublines

Abstract: In the present study, we investigated the possible combined anticancer ability of bee venom (BV) and cisplatin towards two pairs of tumour cell lines: parental cervical carcinoma HeLa cells and their cisplatin-resistant HeLa CK subline, as well as laryngeal carcinoma HEp-2 cells and their cisplatin-resistant CK2 subline. Additionally, we identified several peptides of BV in the BV sample used in the course of the study and determined the exact concentration of MEL. BV applied alone in concentrations of 30 to 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 83 publications
1
18
0
Order By: Relevance
“…These components have known cytotoxic effects towards different cells (Son et al 2007;Oršolić 2012;Gajski and Garaj-Vrhovac 2013) and are likely to be responsible for the effects observed in our study as well. In our previous study, peptides MEL, apamin, MCD peptide and tertiapin were identified as components of BV and we determined the concentration of MEL and its mass fraction in a BV sample, estimating it at 0.19 (Gajski et al 2014). The identified peptides are also in agreement with earlier findings concerning peptide components of BV (Son et al 2007;Oršolić 2012).…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…These components have known cytotoxic effects towards different cells (Son et al 2007;Oršolić 2012;Gajski and Garaj-Vrhovac 2013) and are likely to be responsible for the effects observed in our study as well. In our previous study, peptides MEL, apamin, MCD peptide and tertiapin were identified as components of BV and we determined the concentration of MEL and its mass fraction in a BV sample, estimating it at 0.19 (Gajski et al 2014). The identified peptides are also in agreement with earlier findings concerning peptide components of BV (Son et al 2007;Oršolić 2012).…”
Section: Discussionsupporting
confidence: 89%
“…Until now, it has been demonstrated that BV has the ability to inhibit the growth of several types of cancer cell lines and induce cytotoxic, immunomodulatory, apoptotic and necrotic effects both in vivo and in vitro (Son et al 2007;Oršolić 2012;Gajski et al 2014;Liu et al 2014). Previously, we reported that BV is cytotoxic towards different types of tumour and non- tumour cells in vitro ) with preferential cytotoxicity against tumour cells.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Bee venom makes sense as a complement to cisplatin: it has protective effects in many areas of the body such as the blood and nerves [6]; it is able to inhibit cell growth in tumours [7]; and has even been examined and used in complementary treatments that are necessitated by the effects of chemotherapy, such as allodynia [8] and neuropathy [9]. Cisplatin in combination with bee venom has been successfully used against human cervical and laryngeal carcinoma cells, including their drug-resistant sublines [10], and human glioblastoma [11]. Several studies have found that phospholipase A 2 , another component of bee venom, not only mitigates the negative impact of cisplatin on kidneys [12], but also boosts regulatory T cell (Treg) numbers in the spleen and enhances Treg traffic to the kidneys following cisplatin exposure.…”
Section: Introductionmentioning
confidence: 99%